Analisis Yuridis Pemutusan Sepihak dalam Kasus Perjanjian Kerja Sama Pengelolaan dan Pemanfaatan Limbah B3 oleh PT Chuhatsu Indonesia terhadap PT Tenang Jaya Sejahtera - Zulfariza, Alya Annisa; Pakpahan, Firly Natasha; Rahman, Naziva Azahra; Putri, Audrey Rasya Novianto; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Unilateral termination of agreements is often encountered, where one party unilaterally terminates an agreement that was initially made based on mutual consent. This situation is similar to the case involving PT. Chuhatsu Indonesia and PT. Sejahtera. In addressing this case, the Supreme Court (MA) opined that if one party that has entered into an agreement with another party unilaterally terminates the agreement, the terminating party is deemed to have committed an unlawful act (PMH). The Supreme Court's (MA) opinion is stated in Decision Number 1051 K/Pdt/2014 (PT. Chuhatsu Indonesia vs. PT. Tenang Jaya Sejahtera), dated November 12, 2014. According to the Supreme Court (MA), unilateral termination of an agreement violates Article 1338 of the Indonesian Civil Code (KUHPerdata) and the legal stance it has explained, where the Supreme Court views unilateral termination of an agreement as an unlawful act, which has become a permanent jurisprudence in the Supreme Court. This is because the Supreme Court has consistently applied this legal stance in all rulings involving similar issues since 2014. To further identify this matter, using a juridical method with a legislative approach, the author focuses on analyzing the legal implications of the termination of the agreement by PT. Chuhatsu Indonesia against PT. Tenang Jaya Sejahtera on November 12, 2014.